Decent work in a digital age: a comprehensive review of research and theory - Susanti Saragih; Jann Hidajat Tjakraatmadja; Andika Putra Pratama (Cogent Business & Management, 2024)
Rapid technological change is transforming work, leading to a renewed focus on `decent work'. While research on decent work is extensive, its connection to digitalization remains under-explored. This study presents a systematic review using the PRISMA methodology, analysing 110 relevant studies. The result showed that the research on decent work has significantly increased in the past decade, with diverse perspectives emerging. Three key themes were identified: digital work transformation, inadequate compensation, and work fulfilment. The digital shift has impacted how work is designed, accomplished, and experienced, influencing the perception of decent work. The concept and practices of decent work need adaptation to meet the demands of the digital age. Future research should explore decent work through the lens of self-value/psychology, the impact of digitalization on work design, and the integration of management and organizational theories. This study informs researchers and practitioners on promoting decent work in the digital era.
Keywords: 650; Decent work; quality of work; psychology of working theory; digitalization; management